Die Verantwortung des Arbeitgebers für den sozialen Schutz in Russland Rechtsvergleichende Perspektiven - Becker, Ulrich (Studien aus dem Max-Planck-Institut für Sozialrecht und Sozialpolitik, 2018)
Social insurance thrives, among other things, on the involvement of employers. This cooperation has remained important to the present day. In fact, in some Western European countries, employers are duty bound more than before, for example in cases of work accidents or continued payments of wages in the event of sickness. In the USSR, "employers" were in a different position from the outset: their companies were state-owned and therefore, administrative state duties in the field of social security could be delegated to them at any time. The purpose of these conference proceedings is to investigate how the role of the Russian employer in the social security system has changed compared to the situation during the USSR era. Which legal liability is ascribed to employers today? Does the enforcement of employees' entitlements to social benefits depend on the fulfilment of employers' obligations in the fields of social insurance and occupational safety law? The answer to these questions contributes fundamentally to the understanding of Russian social security law. An analysis of the main aspects of the topic is given from a Russian point of view and subsequently summarised and expanded upon from a German point of view.